Bio-enhancer: A potential input for flowering and post-harvest life of rose (Rosa hybrida) cv. Grand Gala - TRIVEDI, HIMANSHU; KUMAR, PRABHAT; KAPOOR, AJIT; PARWEEN, SHAMA (The Indian Journal of Agricultural Sciences, 2016)
The present investigation was carried out to find the response of different bio-enhancers, i.e. Panchgavya, Jivamrita and vermiwash on flowering and post-harvest attributes of rose (Rose hybrida) cv. Grand Gala. There were three levels of each treatment used . Panchgavya at 0%, 3% and 6% and Jivamrita 0%, 20% and 30% were drenched while vermiwash was sprayed on the plants at 0, 1:5 and 1:10 time dilution. Observations were recorded on flowering and post-harvest attributes in winter season of 2011-12 and 2012-13. Results revealed that 6% Panchgavya + 1:5 times dilution of vermiwash + 30% Jivamrita was found most superior than other treatments and resulted in earliest bud initiation , maximum number of flowers/plant, maximum flower bud length, maximum number of petals/flower, larger flower diameter,duration of flowering flower stem length,and flower yield. Post-harvest attributes, viz. initial diameter of bud at harvesting stage, final diameter of flower in vase, initial weight of bud at harvesting stage, final weight of flower in vase and vase life were found superior with the application of 6%,Panchgavya + 1:5 times dilution of vermiwash + 30% Jivamrita.